A high-performance composite nanofiltration membrane and its preparation method and application
By introducing MOP-SO3Na material into the polyamide nanofiltration membrane and carrying out interfacial polymerization, the problems of insufficient hydrophilicity and poor anti-pollution performance of the polyamide nanofiltration membrane are solved, and higher water flux and separation performance are achieved.
Patent Information
- Application Number
- CN202411360144.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The surface hydrophilicity of existing polyamide nanofiltration membranes is not high, resulting in serious membrane pollution, affecting water flux and separation performance, and the cleaning treatment cost is high and it is easy to damage the membrane structure.
The polyethersulfone ultrafiltration membrane was used as the support layer, and the MOP-SO3Na material was introduced into the polyamide separation layer through interfacial polymerization, improving the hydrophilicity and anti-pollution properties of the membrane.
The water flux and separation performance of the composite nanofiltration membrane are improved, the anti-pollution performance is enhanced, and the cleaning and treatment cost is reduced.
Smart Images

Figure BDA0005064728380000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite membrane materials, and in particular to a high-performance composite nanofiltration membrane and a preparation method and application thereof. Background Art
[0002] Nanofiltration membrane was previously called "low-pressure reverse osmosis membrane" or "loose reverse osmosis membrane". It is a new type of pressure-driven membrane between reverse osmosis membrane and ultrafiltration membrane, with a nanometer pore size. Nanofiltration membrane has the characteristics of lower operating pressure than reverse osmosis membrane and different separation effects for monovalent and multivalent ions. With the above characteristics and simple and easy-to-operate separation process, nanofiltration membrane is widely used in water treatment and environmental protection fields.
[0003] The quality of nanofiltration membrane materials directly determines the performance of the nanofiltration membrane separation process. Currently, commercial nanofiltration membranes are mainly polyamide nanofiltration membranes. Although the current polyamide nanofiltration membranes already have good separation performance, there are still some defects in their separation technology, such as: the low surface hydrophilicity leads to serious membrane contamination, which in turn affects the water flux and separation performance of the nanofiltration membrane. Cleaning the membrane can solve the membrane contamination problem to a certain extent, but this not only increases the cost, but also the cleaning process of the membrane can easily damage the surface structure of the membrane. Therefore, how to improve the anti-pollution performance of polyamide nanofiltration membranes, improve the membrane flux and separation performance of polyamide nanofiltration membranes are technical problems that need to be solved in this field. Summary of the invention
[0004] In view of this, the present invention provides a method for preparing a high-performance composite nanofiltration membrane, comprising the following steps:
[0005] (1) Prepare polyethyleneimine (PEI) aqueous solution and trimesoyl chloride (TMC) n-hexane solution, and mix MOP-SO 3 The Na material was placed in a polyethyleneimine (PEI) aqueous solution and ultrasonically treated at room temperature until MOP-SO 3 The Na material is uniformly dispersed in the aqueous solution;
[0006] (2) Dispersed MOP-SO 3 The Na material aqueous solution is poured into a reaction container with a polyethersulfone ultrafiltration membrane at the bottom, and the solution in the reaction container is filtered. After the filtration is completed, the surface covered with MOP-SO is taken out. 3 The polyethersulfone ultrafiltration membrane made of Na material is dried at room temperature to obtain a dry membrane;
[0007] (3) The dried membrane is placed in a n-hexane solution of trimesoyl chloride (TMC) to carry out an interfacial polymerization reaction, and then the membrane after the reaction is allowed to stand in the air for 15-30 minutes to form a polyamide separation membrane layer, and then placed in deionized water at room temperature to terminate the reaction, thereby obtaining a composite nanofiltration membrane material.
[0008] Furthermore, the concentration of the polyethyleneimine (PEI) aqueous solution in step (1) is 0.1-1.0% (W / V).
[0009] Furthermore, the concentration of the trimesoyl chloride (TMC) n-hexane solution in step (1) is 0.1-0.5% (W / V).
[0010] Furthermore, the MOP-SO in step (1) 3 The mass concentration of the Na material is 0.001-0.005%.
[0011] Furthermore, the ultrasonic treatment time in step (1) is 15-25 minutes.
[0012] Furthermore, the preparation method of the polyethersulfone ultrafiltration membrane in step (2) comprises the following steps: adding polyethersulfone (PES), N,N-dimethylformamide (DMF) and polyethylene glycol (PEG) into a reaction container in proportion, mixing evenly, stirring and keeping warm for 8-12 hours at a temperature of 50-80°C, and then standing for 12-24 hours to form a casting liquid, vacuum degassing the casting liquid, placing the completely degassed casting liquid on the surface of a dry glass plate, using a wet film preparation device (thickness 300μm×length 150mm) to stably and evenly scrape the film, and then soaking it in deionized water at room temperature for 1-5 minutes. After the membrane is solidified, a polyethersulfone ultrafiltration membrane is obtained.
[0013] Furthermore, the time of the interfacial polymerization reaction in step (3) is 150-200s.
[0014] The present invention also provides a high-performance composite nanofiltration membrane prepared according to the method and applications of the high-performance composite nanofiltration membrane in the fields of wastewater treatment, seawater desalination and dye desalination.
[0015] Compared with the prior art, the present invention has the following beneficial effects: the present invention selects polyethersulfone ultrafiltration membrane as the support layer, and utilizes the interfacial polymerization method to form MOP-SO 3 The introduction of Na material into the polyamide separation layer improves the hydrophilicity and anti-fouling properties of the composite nanofiltration membrane and increases the water flux of the composite nanofiltration membrane. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0017] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the raw materials and auxiliary agents are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.
[0018] The NaH in the following examples 2 (5-SO 3 -l,3-BDC) and copper acetate (Cu(CH 3 COO 2 ·H 2 O were purchased from Beijing Bailingwei Technology Co., Ltd.
[0019] Example 1
[0020] A method for preparing a high-performance composite nanofiltration membrane, the specific steps are as follows:
[0021] (1) 253 mg NaH 2 (5-SO 3 -1,3-BDC) was mixed with 6 ml of methanol to form solution A; 220 mg of copper acetate (Cu(CH 3 COO 2 ·H 2 O was dispersed in a mixed solution of 20 ml MeOH / DMA (v:v=1:1) to form solution B; solution A and solution B were stirred at room temperature until fully mixed to obtain a mixture, 6.0 ml DMA was added to the mixture, and the mixture was allowed to stand at room temperature for 8 days. After the standing period, the solid product in the reaction container was collected and washed with ethanol and DMA respectively to obtain MOP-SO 3 Na material, spare;
[0022] (2) Prepare a 0.5% aqueous solution of polyethyleneimine and a 0.25% n-hexane solution of trimesoyl chloride. 3 Na material was placed in a polyethyleneimine aqueous solution, and the MOP-SO 3 The concentration of Na material was 0.005%, the average length was 10-20 nm, and it was sonicated at room temperature for 20 min until MOP-SO 3 The Na material is evenly dispersed in the aqueous solution and set aside;
[0023] (3) Add polyethersulfone, polyethylene glycol and N,N-dimethylformamide into a beaker in a mass ratio of 5:2:3, mix well, stir and keep warm at 60°C for 10 hours, then let stand for 20 hours to form a transparent casting solution, perform vacuum degassing on the casting solution, place the degassed casting solution on a dry glass plate, use a wet film preparation device (thickness 300 μm × length 150 mm) to stably and evenly scrape the film, then soak in deionized water at room temperature for 2 minutes, and after the film is solidified, obtain a polyethersulfone ultrafiltration membrane for standby use;
[0024] (4) Spread the polyethersulfone ultrafiltration membrane described in step (3) on the bottom of a clean and dry beaker, and then pour the MOP-SO 3 The aqueous solution of Na material is filtered until the liquid is drained. After the filtration is completed, the surface covered with MOP-SO is taken out. 3 The polyethersulfone ultrafiltration membrane made of Na material is dried at room temperature until there is no visible free water on the membrane surface to obtain a dry membrane;
[0025] (5) Immersing the dried membrane described in step (4) in a n-hexane solution of trimesoyl chloride to cause an interfacial polymerization reaction at room temperature for 180 seconds. After the interfacial polymerization reaction is completed, the membrane after the reaction is allowed to stand in the air for 20 minutes to form a polyamide separation membrane layer. The polyamide separation membrane layer is then immersed in deionized water at room temperature to terminate the reaction, thereby obtaining a composite nanofiltration membrane material.
[0026] Example 2
[0027] A method for preparing a high-performance composite nanofiltration membrane, the specific steps are as follows:
[0028] (1) 253 mg NaH 2 (5-SO 3 -1,3-BDC) was mixed with 6 ml of methanol to form solution A; 220 mg of copper acetate (Cu(CH 3 COO 2 ·H 2 O was dispersed in a mixed solution of 20 ml MeOH / DMA (v:v=1:1) to form solution B; solution A and solution B were stirred at room temperature until fully mixed to obtain a mixture, 6.0 ml DMA was added to the mixture, and the mixture was allowed to stand at room temperature for 8 days. After the standing period, the solid product in the reaction container was collected and washed with ethanol and DMA respectively to obtain MOP-SO 3 Na material, spare;
[0029] (2) Prepare a 0.1% polyethyleneimine aqueous solution and a 0.1% trimesoyl chloride n-hexane solution, and mix MOP-SO3 Na material was placed in a polyethyleneimine aqueous solution, and the MOP-SO 3 The concentration of Na material was 0.001%, the average length was 10-20 nm, and it was sonicated at room temperature for 15 min until MOP-SO 3 The Na material is evenly dispersed in the aqueous solution and set aside;
[0030] (3) Add polyethersulfone, polyethylene glycol and N,N-dimethylformamide into a beaker in a mass ratio of 5:2:3, mix well, keep warm at 50°C for 8 hours while stirring, and then let it stand for 12 hours to form a transparent casting solution, perform vacuum degassing on the casting solution, place the degassed casting solution on the surface of a dry glass plate, and use a wet film preparation device (thickness 300 μm × length 150 mm) to stably and evenly scrape the film, then soak it in deionized water at room temperature for 2 minutes, and after the film is solidified, obtain a polyethersulfone ultrafiltration membrane for standby use;
[0031] (4) Spread the polyethersulfone ultrafiltration membrane described in step (3) on the bottom of a clean and dry beaker, and then pour the MOP-SO 3 The aqueous solution of Na material is filtered until the liquid is drained. After the filtration is completed, take out the surface covered with MOP-SO 3 The polyethersulfone ultrafiltration membrane made of Na material is dried at room temperature until there is no visible free water on the membrane surface to obtain a dry membrane;
[0032] (5) Immersing the dried membrane described in step (4) in a n-hexane solution of trimesoyl chloride to cause an interfacial polymerization reaction at room temperature for 150 seconds. After the interfacial polymerization reaction is completed, the membrane after the reaction is allowed to stand in the air for 15 minutes to form a polyamide separation membrane layer. The polyamide separation membrane layer is then immersed in deionized water at room temperature to terminate the reaction, thereby obtaining a composite nanofiltration membrane material.
[0033] Example 3
[0034] A method for preparing a high-performance composite nanofiltration membrane, the specific steps are as follows:
[0035] (1) 253 mg NaH 2 (5-SO 3 -1,3-BDC) was mixed with 6 ml of methanol to form solution A; 220 mg of copper acetate (Cu(CH 3 COO 2 ·H 2O was dispersed in a mixed solution of 20 ml MeOH / DMA (v:v=1:1) to form solution B; solution A and solution B were stirred at room temperature until fully mixed to obtain a mixture, 6.0 ml DMA was added to the mixture, and the mixture was allowed to stand at room temperature for 8 days. After the standing period, the solid product in the reaction container was collected and washed with ethanol and DMA respectively to obtain MOP-SO 3 Na material, spare;
[0036] (2) Prepare a 1.0% polyethyleneimine aqueous solution and a 0.5% trimesoyl chloride n-hexane solution, and mix MOP-SO 3 Na material was placed in a polyethyleneimine aqueous solution, and the MOP-SO 3 The concentration of Na material was 0.002% and the average length was 10-20 nm. It was ultrasonicated at room temperature for 25 min until MOP-SO 3 The Na material is evenly dispersed in the aqueous solution and set aside;
[0037] (3) Add polyethersulfone, polyethylene glycol and N,N-dimethylformamide into a beaker in a mass ratio of 5:2:3, mix well, keep warm at 80°C for 12 hours while stirring, and then stand for 24 hours to form a transparent casting solution, perform vacuum degassing on the casting solution, place the degassed casting solution on the surface of a dry glass plate, and use a wet film preparation device (thickness 300 μm × length 150 mm) to stably and evenly scrape the film, then soak it in deionized water at room temperature for 5 minutes, and after the film is solidified, obtain a polyethersulfone ultrafiltration membrane for standby use;
[0038] (4) Spread the polyethersulfone ultrafiltration membrane described in step (3) on the bottom of a clean and dry beaker, and then pour the MOP-SO 3 The aqueous solution of Na material is filtered until the liquid is drained. After the filtration is completed, take out the surface covered with MOP-SO 3 The polyethersulfone ultrafiltration membrane made of Na material is dried at room temperature until there is no visible free water on the membrane surface to obtain a dry membrane;
[0039] (5) Immersing the dried membrane described in step (4) in a n-hexane solution of trimesoyl chloride to cause an interfacial polymerization reaction at room temperature for 200 seconds. After the interfacial polymerization reaction is completed, the membrane after the reaction is allowed to stand in the air for 30 minutes to form a polyamide separation membrane layer. The polyamide separation membrane layer is then immersed in deionized water at room temperature to terminate the reaction, thereby obtaining a composite nanofiltration membrane material.
[0040] Comparative Example 1
[0041] The difference from Example 1 is that no MOP-SO is added. 3Na material, and the remaining steps are consistent with Example 1.
[0042] Comparative Example 2
[0043] The difference from Example 1 is that MOP-SO 3 The concentration of Na material is 0.01wt%, and the remaining steps are consistent with Example 1.
[0044] Comparative Example 3
[0045] The difference from Example 1 is that the time of the interfacial polymerization reaction is 120 s, and the other steps are consistent with Example 1.
[0046] The performance tests of the membrane materials of Examples 1-3 and Comparative Examples 1-3 are as follows:
[0047] 1. Hydrophilicity test of membrane materials
[0048] Contact angle, also known as wetting angle, is an important parameter for testing the hydrophilicity and hydrophobicity of a material surface. This test uses the JC-2000C1 contact angle meter to characterize the hydrophilicity and hydrophobicity of the membrane surface. The larger the contact angle, the worse the hydrophilicity of the sample surface, and the smaller the contact angle, the better the hydrophilicity of the membrane sample.
[0049] The specific process of the hydrophilicity test is as follows: the sample is cut into a 3×2cm rectangle, ultrasonically cleaned with deionized water for 15 minutes, and transferred to a 60℃ oven for drying to obtain the sample to be tested for standby use; the ambient temperature is maintained at 25℃, and 5μL of deionized water is transferred with a dry and clean pipette to drop on the surface of the flat sample to be tested. After the drop is completed, the image is quickly saved using the image capture function of the instrument, and then the contact angle data of the sample to be tested is obtained by computer calculation of the three-point method. Five points are randomly selected on the surface of the sample to be tested to measure the contact angle, and the average value of the five measurements is finally selected.
[0050] The hydrophilicity of the membrane materials prepared in Examples 1-3 and Comparative Examples 1-3 was measured respectively. The results showed that the contact angle of the membrane material in Example 1 was 38.3°, the contact angle of the membrane material in Example 2 was 39.2°, and the contact angle of the membrane material in Example 3 was 37.5°; the contact angle of the membrane material in Comparative Example 1 was 78.2°, the contact angle of the membrane material in Comparative Example 2 was 45.2°, and the contact angle of the membrane material in Comparative Example 3 was 48.4°. It can be seen that the introduction of a specific proportion of MOP-SO in the polyamide separation layer 3 Na materials and conducting interfacial polymerization under specific conditions can effectively improve the hydrophilicity of nanofiltration membrane materials.
[0051] 2. Membrane separation performance test
[0052] The specific test process of separation performance test is as follows: The separation performance of the membrane sample is tested using a triple high-pressure flat membrane test device (FlowMem0021-HP). After the membrane sample is rinsed with pure water several times, it is placed in a test pool of 4cm×6cm for separation performance test. To ensure the stability of the membrane sample test performance, the sample to be tested is pre-pressed at 0.6MPa for 10min before each test to achieve flux stability. The effective filtration area of the sample is A=24cm 2 , the circulation flow rate is 5 LPM, and the test temperature is 25 ± 0.5 ° C. The retention rate is used as a parameter to evaluate the separation performance of the membrane sample.
[0053] In this experiment, the concentration of Na2O3 was 500 mg / L. 2 SO 4 The feed liquid is used as the feed solution. The conductivity of the feed liquid and the raw material liquid is tested respectively, and the corresponding concentration is calculated according to the standard (concentration-conductivity) curve. The calculation method of the retention rate is as shown in Formula I,
[0054]
[0055] In formula Ⅰ, R-retention rate, %; C p -Permeate concentration, mg·L -1 ; C f - Raw material solution concentration, mg·L -1 .
[0056] The separation performance of the membrane materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested respectively, and the results showed that:
[0057] Example 1 Membrane material for Na 2 SO 4 The rejection rate of the membrane material in Example 2 is 99.8%. 2 SO 4 The rejection rate of the membrane material in Example 3 is 99.6%. 2 SO 4 The rejection rate of the membrane material in Comparative Example 1 is 99.3%; 2 SO 4 The rejection rate of the membrane material in Comparative Example 2 is 73.5%. 2 SO 4 The rejection rate of the membrane material in Comparative Example 3 is 85.1%. 2 SO 4 The interception rate was 89.2%.
[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high-performance composite nanofiltration membrane, characterized in that: The following steps are involved: (1) preparing a polyethyleneimine aqueous solution and a trimesoyl chloride n-hexane solution, placing the MOP-SO3Na material into the polyethyleneimine aqueous solution, and performing ultrasonic treatment at room temperature until the MOP-SO3Na material is uniformly dispersed in the aqueous solution; (2) pouring the dispersed MOP-SO3Na material aqueous solution into a reaction container with a polyethersulfone ultrafiltration membrane at the bottom, filtering the solution in the reaction container, and after the filtration is completed, taking out the polyethersulfone ultrafiltration membrane covered with the MOP-SO3Na material on the surface, and drying it at room temperature to obtain a dry membrane; (3) placing the dried membrane in a hexane solution of trimesoyl chloride to carry out an interfacial polymerization reaction, then placing the membrane after the reaction in air for 15-30 minutes to form a polyamide separation membrane layer, and then placing it in deionized water at room temperature to terminate the reaction, thereby obtaining a composite nanofiltration membrane material; The preparation method of the MOP-SO3Na material in step (1) is as follows: 253 mg NaH2(5-SO3-1,3-BDC) is mixed with 6 ml methanol to form solution A; 220 mg copper acetate Cu(CH3COO)2·H2O is dispersed in 20 ml MeOH / DMA mixed solution (v:v=1:1) to form solution B; solution A and solution B are stirred at room temperature until fully mixed to obtain a mixture, 6.0 ml DMA is added to the mixture, and the mixture is allowed to stand at room temperature for 8 days. After the standing period, the solid product in the reaction container is collected, and washed with ethanol and DMA respectively to obtain the MOP-SO3Na material.
2. The method for preparing a high-performance composite nanofiltration membrane according to claim 1, characterized in that: The concentration of the polyethyleneimine aqueous solution in step (1) is 0.1-1.0%.
3. The method for preparing a high-performance composite nanofiltration membrane according to claim 1, characterized in that: The concentration of the trimesoyl chloride n-hexane solution in step (1) is 0.1-0.5%.
4. The method for preparing a high-performance composite nanofiltration membrane according to claim 1, characterized in that: The concentration of the MOP-SO3Na material in step (1) is 0.001-0.005%.
5. The method for preparing a high-performance composite nanofiltration membrane according to claim 1, characterized in that: The ultrasonic treatment time in step (1) is 15-25 minutes.
6. The method for preparing a high-performance composite nanofiltration membrane according to claim 1, characterized in that: The preparation method of the polyethersulfone ultrafiltration membrane in step (2) comprises the following steps: adding polyethersulfone, polyethylene glycol and N,N-dimethylformamide into a reaction container in proportion, mixing evenly, stirring and keeping warm for 8-12 hours at a temperature of 50-80°C, and then standing for 12-24 hours to form a casting liquid, vacuum degassing the casting liquid, placing the degassed casting liquid on the surface of a dry glass plate, scraping the film stably and evenly with a wet film preparation device, and then soaking it in deionized water at room temperature for 1-5 minutes. After the film is solidified, a polyethersulfone ultrafiltration membrane is obtained.
7. The method for preparing a high-performance composite nanofiltration membrane according to claim 1, characterized in that: The time of the interfacial polymerization reaction in step (3) is 150-200s.
8. A high performance composite nanofiltration membrane prepared according to the method according to any one of claims 1 to 7.
9. The high-performance composite nanofiltration membrane prepared by the method according to any one of claims 1 to 7, or the use of the high-performance composite nanofiltration membrane according to claim 8 in the fields of wastewater treatment, seawater desalination and dye desalination.
Citation Information
Patent Citations
Composite nanofiltration membrane for magnesium-lithium separation as well as preparation method and application of composite nanofiltration membrane
CN118001941A
Cited By
Preparation method for preparing anti-pollution and high-permeability nanofiltration membrane based on graft modification
CN122352046A